2017
DOI: 10.1016/j.physletb.2016.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scalar field mass on gravitating charged scalar solitons and black holes in a cavity

Abstract: We study soliton and black hole solutions of Einstein charged scalar field theory in cavity. We examine the effect of introducing a scalar field mass on static, spherically symmetric solutions of the field equations. We focus particularly on the spaces of soliton and black hole solutions, as well as studying their stability under linear, spherically symmetric perturbations of the metric, electromagnetic field, and scalar field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…If the system has electric charge, we can also have static black hole bomb systems [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. All we need is a complex scalar field with charge q scattering a Reissner-Nordström black hole with chemical potential µ that is placed inside a box that reflects the scalar waves.…”
mentioning
confidence: 99%
“…If the system has electric charge, we can also have static black hole bomb systems [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. All we need is a complex scalar field with charge q scattering a Reissner-Nordström black hole with chemical potential µ that is placed inside a box that reflects the scalar waves.…”
mentioning
confidence: 99%
“…Including charged scalars, boson stars and hairy black holes in a cavity were considered in [21][22][23][24], which showed that the phase structure of the gravity system in a cavity is strikingly similar to that of holographic superconductors in the AdS gravity. The stabilities of solitons, stars and black holes in a cavity were also studied in [25][26][27][28][29][30][31][32]. It was found that the nonlinear dynamical evolution of a charged black hole in a cavity could end in a quasi-local hairy black hole.…”
mentioning
confidence: 99%
“…Our compact theorem therefore reveals the interesting fact that, as opposed to stationary scalar fields [12,13,[27][28][29][30][31], static self-gravitating scalar fields whose nonlinear selfinteraction potential V (ψ 2 ) is a monotonically increasing function of its argument cannot form spatially regular asymptotically flat boson stars.…”
Section: Discussionmentioning
confidence: 99%